Reflecting on Philosophical Grammar - Padilla, Jesús (2012)
The aim of this paper is to analyze Wittgenstein’s philosophical grammar in the Middle Period. The paper examines the thesis that grammar is not responsible for reality. It investigates the role that rules play in this context and how they determine meaning. Special focus shall be put on arbitrary rules. Therefore, we shall develop a thesis of vagueness with special emphasis on perspicuous representation.